Electronic compensation-induced stabilization of carbon dots@PMMA under UV aging. (23rd October 2017) - Chen, Xiang-Yang; Yang, Xue-Chun; Zhang, Zhi-Jun; Yao, He-Liang; Zhang, Lin-Lin; Lu, Ping; Jin, Teng-Teng; Xu, Fang-Fang; Zhao, Jing-Tai
Abstract : As-prepared FOCDs could enhance the stability of optical polymers under UV aging through timely electron compensation with no deterioration in transparency. Abstract : This communication reports the synthesis of CC functionalized oleophilic carbon dots (FOCDs). The as-prepared FOCDs could enhance the stability of optical polymer against UV aging while no obvious effect on optical transparency.